A Deep Nasopharyngeal Swab Versus Nonendoscopic Bronchoalveolar Lavage for Isolation of Bacterial Pathogens from Preweaned Calves With Respiratory Disease. (19th April 2017) - Van Driessche, L.; Valgaeren, B.R.; Gille, L.; Boyen, F.; Ducatelle, R.; Haesebrouck, F.; Deprez, P.; Pardon, B.
Abstract : Background: Nonendoscopic bronchoalveolar lavage (BAL) is a practical alternative for a deep nasopharyngeal swab (DNS) to sample the airways of a large number of calves in a short period of time. The extent of commensal overgrowth and agreement of BAL with DNS culture results in preweaned calves are unknown. Objectives: To compare commensal overgrowth and bacterial culture results between DNS and BAL samples. Animals: A total of 183 preweaned calves (144 with bovine respiratory disease and 39 healthy animals). Methods: Cross‐sectional study. Deep nasopharyngeal swab and BAL samples were taken from each calf and cultured to detect Pasteurellaceae and Mycoplasma bovis . Agreement and associations between culture results of DNS and BAL samples were determined by kappa statistics and logistic regression. Results: Bronchoalveolar lavage samples were less often polymicrobial, more frequently negative and yielded more pure cultures compared to DNS, leading to a clinically interpretable culture result in 79.2% of the cases compared to only in 31.2% of the DNS samples. Isolation rates were lower in healthy animals, but not different between DNS and BAL samples. Only Histophilus somni was more likely to be isolated from BAL samples. In clinical cases, a polymicrobial DNS culture result did not increase the probability of a polymicrobial BAL result by ≥30%, nor did it influence the probability of a negative culture. A significant herd effect was noted for all observed relationships. Conclusions and Clinical Relevance: Nonendoscopic BAL samples are far less overgrown by bacteria compared to DNS samples under the conditions of this study, facilitating clinical interpretation and resulting in a higher return on investment in bacteriologic culturing.